Navigating Culture Shock: The Cross-Cultural Adaptation Experiences of Balinese Employees Working on Cruise Ship - I Gusti Ngurah Agung suprastayasa; Teguh Hadi Sukarno (Journal of Tourism and Hospitality Analysis (JoTHA), 2026)
The study aims to explore the culture shock experienced by Balinese employees working on cruise ships and identify the strategies they employ to adapt to a culturally diverse workplace. A descriptive qualitative approach was adopted, with data collected through semi-structured, in-depth interviews involving eight Balinese cruise ship employees selected using chain referral sampling. The data were analyzed using thematic coding to identify recurring patterns and key adaptation experiences. The findings reveal that participants experienced culture shock primarily during the early stages of employment, characterized by homesickness, language barriers, communication difficulties, unfamiliar workplace norms, and differences in cultural values and social interactions. Despite these challenges, participants gradually adapted by improving their English communication skills, developing intercultural competence, building supportive relationships with fellow crew members, and maintaining their Balinese cultural identity while embracing cultural diversity. The study highlights that successful adaptation depends not only on individual resilience but also on organizational support through orientation programs, intercultural communication training, mentoring, and psychological assistance. The findings contribute to the literature on culture shock by providing insights into the experiences of Balinese cruise ship employees, a population that has received limited scholarly attention. The study also offers practical recommendations for cruise companies to develop more effective cross-cultural management practices that enhance employee well-being, job satisfaction, and service performance.